1994
DOI: 10.1507/endocrj.41.535
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary Function in Patients with Rathke's Cleft Cyst: Significance of Surgical Management.

Abstract: Abstract.The pituitary function of patients with Rathke's cleft cyst before and after surgery was investigated to clarify the significance of surgery and operative indications.The authors have treated 19

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
89
3
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(100 citation statements)
references
References 10 publications
6
89
3
2
Order By: Relevance
“…The low recovery rates are thought to be associated with an inflammatory process caused by the cyst contents, which may result in irreversible damage to the adjacent hypophysis. 7,8,12,25,33,43,54 Our results show that preoperative headache and visual dysfunction were resolved in 85% and 95% of patients, and both rates compare favorably with the findings of other studies. However, we achieved better resolution in the patients with hypopituitarism and DI than other series of similar sample size (55% and 65%, respectively).…”
Section: Outcome Analysissupporting
confidence: 89%
“…The low recovery rates are thought to be associated with an inflammatory process caused by the cyst contents, which may result in irreversible damage to the adjacent hypophysis. 7,8,12,25,33,43,54 Our results show that preoperative headache and visual dysfunction were resolved in 85% and 95% of patients, and both rates compare favorably with the findings of other studies. However, we achieved better resolution in the patients with hypopituitarism and DI than other series of similar sample size (55% and 65%, respectively).…”
Section: Outcome Analysissupporting
confidence: 89%
“…Secondly, his polyuria and polydipsia improved and he became not to need DDAVP three months after the treatment with interferon α. It is known that CDI does not tend to ameliorate even if primary disease such as inflammation [4], infiltration [5,6] or tumor [7,8], is successfully treated.…”
mentioning
confidence: 99%
“…However, when it grows more than 1 cm or infl ammatory changes develop, various symptoms may occur [8]. Mechanical compression of the pituitary gland by the cyst, as well as infl ammation itself, may play a major role in causing pituitary dysfunction in RCC patients [8].…”
Section: Discussionmentioning
confidence: 99%
“…The reserve of the pituitary gland decreases, resulting in an empty sella fi lled with necrotic tissue in the fi nal stages [3,4]. In small number of studies, the hypopituitarism was found in 39-100% of patients with RCC [8][9][10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation